Penggunaan Gadget Terhadap Perilaku dan Intensitas Komunikasi Keluarga (Studi Kasus Kecamatan Soreang Kota Parepare) : Penggunaan Gadget Terhadap Perilaku dan Intensitas Komunikasi Keluarga (Studi Kasus Kecamatan Soreang Kota Parepare) - A. Nurul Mutmainnah; Nidaul Islam (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
he study of this article explains the communication behavior of family members after the onset of the gadget. In the current technological development, gadgets become tools that are not separated by humans in everyday life. Similarly, with family members can not be separated with gaget to support their daily activities. Communication is the key to family harmony, but the presence of gadgets has an influence on family communication behavior. This article uses qualitative research methods by collecting observation data, in-depth interviews, and other research supporting data. the results of this study found that the communication behavior of family members in using gadgets is divided into two, namely proactive in communication, and reactive in family communication. Family communication in maintaining harmony is shown by the unctioning of parents in educating and always paying attention to their children, either by direct communication or through gadgets. Thus, the family remains harmonious because family communication continues despite the presence of a gadget.